2005
DOI: 10.1093/molbev/msi233
|View full text |Cite
|
Sign up to set email alerts
|

Recombination Shapes the Natural Population Structure of the Hyperthermophilic Archaeon Sulfolobus islandicus

Abstract: Although microorganisms make up the preponderance of the biodiversity on Earth, the ecological and evolutionary factors that structure microbial populations are not well understood. We investigated the genetic structure of a thermoacidophilic crenarchaeal species, Sulfolobus islandicus, using multilocus sequence analysis of six variable protein-coding loci on a set of 60 isolates from the Mutnovsky region of Kamchatka, Russia. We demonstrate significant incongruence among gene genealogies and a lack of associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 58 publications
7
84
0
Order By: Relevance
“…Strains were chosen to represent different geothermal areas within LNP and YNP, as shown in Table 1. Mutnovsky strains were chosen to represent parental and recombinant members of the population, as described by Whitaker et al (72). Each genome was sequenced by the Department of Energy (DOE) Joint Genome Institute through standard Sanger sequencing methods.…”
Section: Methodsmentioning
confidence: 99%
“…Strains were chosen to represent different geothermal areas within LNP and YNP, as shown in Table 1. Mutnovsky strains were chosen to represent parental and recombinant members of the population, as described by Whitaker et al (72). Each genome was sequenced by the Department of Energy (DOE) Joint Genome Institute through standard Sanger sequencing methods.…”
Section: Methodsmentioning
confidence: 99%
“…Such a rapid drop in frequency should limit efficient exchange of DNA to closely related genomes, as expected within genotypic clusters, and might play a role in maintaining the cohesion of clusters. Although such relationships have been shown for several, divergent groups of bacteria, in some archaea, the requirement for short, identical DNA stretches seems to be absent (Grogan and Stengel 2008;Naor et al 2012), even though environmental observations support decreased rates of recombination across clusters (Whitaker et al 2005;Williams et al 2012). Moreover, recent comparison of very closely related genomes has also shown that very little sequence similarity appears to be required for integration of long stretches of highly divergent DNA (including single nucleotide changes and structural variants) into the genome (Mell et al 2011;Cordero et al 2012a), although the mechanisms remain unclear.…”
Section: Microbial Speciationmentioning
confidence: 90%
“…Subsequently, MLST-based analyses provided evidence for genetic recombination in the halophilic archaeon Halorubrum sp (25) and the thermoacidophilic archaeon Sulfolobus islandicus (7). Results documenting recombination in F. acidarmanus suggest that mosaic genome structure may be a common feature of natural archaeal populations.…”
Section: Figmentioning
confidence: 99%